The “Operación Sitio” and the Construction of the Popular Periphery of Santiago de Chile (1965-1970); a “Operación Sitio” E a Construção Da Periferia Popular de Santiago Do Chile (1965-1970); la Operación Sitio y la Construcción de la Periferia Popular de Santiago de Chile (1965-1970) - Castillo-Braithwaite, S (Universidad de Chile, 2025)
Operación Sitio, implemented during the Christian Democratic government of Eduardo Frei Montalva (1965–1970), significantly transformed the periphery of Santiago de Chile. This housing program is analyzed as a field of political and technical dispute, combining a historical analysis of primary and secondary sources with a morphological examination of the housing complexes built in the capital. The results show that the program underwent significant changes, shaped by social pressures, governmental decisions, and technical rationalities. Three main phases were identified, distinguished by the types of housing solutions provided, execution times, and program scope. The morphological analysis revealed that approximately 80,000 lots were delivered in Santiago. At the metropolitan scale, the program’s urban objectives were only partially achieved, whereas at the neighborhood level, it succeeded in creating housing complexes organized on 9 m×18 m lots, inspired by the neighborhood unit and equipped with services. In dialogue with studies on peripheral urbanization in Latin America, this case provides insight into the role of the State in the production of working-class neighborhoods, highlighting the role of architects and urban planners, as well as entrepreneurs, political actors, and residents in shaping cities during the sixties. © 2025 Universidad de Chile. All rights reserved.